Madrasah Aliyah Teacher Performance: Survey at MAN 1 South Konawe (Kinerja Guru Madrasah Aliyah : Survey di MAN 1 Konawe Selatan) - Nurmaliana, Nurmaliana; Syahrul, Syahrul; Supriyanto, Supriyanto (Shautut Tarbiyah-IAIN Kendari, 2024)
This article aims to describe and analyze the influence of the leadership of the madrasah principal on teacher performance at MAN 1 Konawe Selatan. The study was conducted quantitatively with a survey method of 37 teachers. Data analysis used descriptive statistical procedures and inferential statistics. The results of the study showed that the leadership of the principal of MAN 1 was perceived well by the teachers, where the madrasah principal showed high characteristics in influencing, guiding, encouraging, directing, and motivating. Teacher performance is in the good category, which can be measured in the dimensions of learning activity planning, implementation of learning activities, learning evaluation, and follow-up. The leadership of the madrasah principal who is perceived well by teachers has a significant influence on their performance. This study suggests the importance of continuous improvement of teacher competence and continuous improvement of leadership practices in madrasah aliyah.Keywords:     Madrasah Principal Leadership, Teacher Performance